SMART GOVERNMENT MELALUI APLIKASI E-LAPOR DALAM MEWUJUDKAN BANTUL SMART CITY - Pakpahan, Milton; Zain, Herlina Muzanah; Estrada, Francois Joseph Koda; Al Jannah, Dejehave (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2025)
This study aims to analyze the implementation of Smart Government policy through the utilization of the E-Lapor Bantul application as an innovation in digital public service delivery within the framework of Smart City development in Bantul Regency. Employing a qualitative research approach, data were collected through in-depth interviews, participatory observation, and document analysis. The analytical model is based on Merilee S. Grindle’s policy implementation framework, which emphasizes two key dimensions: the content of policy and the context of implementation. The findings reveal that the implementation of E-Lapor Bantul has contributed positively to improving the efficiency of complaint handling processes, enhancing bureaucratic transparency, and fostering public participation in local governance. However, the study also identifies several challenges, particularly the limited public outreach and responsiveness from certain government agencies. The research concludes that the success of E-Lapor Bantul’s implementation is shaped by the involvement of key actors, availability of supporting resources, and effective cross-sectoral coordination strategies. Nevertheless, further efforts are needed to strengthen public education and system integration in order to achieve a more adaptive and sustainable digital public service system.